Relevansi Pemikiran Al-Ghazali dan William James dalam Pendidikan Karakter melalui Program Orientasi Santri Baru - Eny Maria Qonita; Akhmad Nurul Kawakip (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This research examines the relevance of character education from the perspectives of Al-Ghazali and William James in the 40-Day Ta'aruf Programme at Al-Yasini Integrated Islamic Boarding School, Pasuruan. This programme aims to help new santri adapt to pesantren life while forming religious and independent characters. Using a descriptive qualitative approach, this study explores the implementation of the programme and its relationship with Al-Ghazali's theory of character education which emphasises tazkiyatun nafs, habituation to worship, and good manners, and William James' psychology of religion which highlights religious experience as a transformational personal process. The results show that the 40-Day Ta'aruf Program is effective in shaping religious character through habituation of worship, internalisation of moral values, and independence training. In addition, this programme helps santri develop psychological resilience and emotional and social adaptability, as described by William James. In conclusion, the integration of Al-Ghazali and William James' perspectives in this programme proves that a spirituality-based approach has a significant role in individual character building. These findings provide recommendations for the development of faith-based character education in various educational institutions.